Perilaku Migrasi Sikep Madu-Asia dalam Pemanfaatan Lanskap di Flores Bagian Timur, Indonesia Berdasarkan Data Satellite-tracking - Syartinilia Syartinilia; Risco Noverio Rafael; Hiroyoshi Higuchi (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2020)
Raptor migration is complex phenomenon of migration which involving of millions of individual birds flying hundreds or thousands kilometers, between breeding habitat and wintering habitat. Migratory behavior consisted of period, route, and other aspects that affect the ecology of migratory birds. Pernis ptylorhynchus, Oriental honey-buzzard (OHB) is one of migratory raptors which have satellite tracked by ARGOS since 2003. Eastern part of Flores Islands consisted of small islands (23 islands) were identified as OHB’s migratory path to reach their wintering habitats in Kupang and Timor Island. This study has aimed to identify and analyze the OHB’s migratory behavior in Eastern part of Flores Islands. Four individuals OHB have satellite tracked in the period of 2007-2012 were used as main data for analyzing their migratory behavior. There was no particular pattern found on the way of OHBs selected islands for their stopover site because of the existence of small islands cluster provide variety of route for each OHBs. The length of their stay found relatively constant every year and tend to be stay longer on larger islands than the smaller one such as Flores Island and Lembata Island. This is apparently due to the larger islands provide more food supply than smaller islands.